The incentive to participate in open source projects: A signaling approach - Yossi Spiegel (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2008)
This paper examines the incentive of unpaid programmers to contribute to open source software (OSS) projects in order to signal their talents. The analysis shows that if programmers contribute to OSS projects at all, then generically there are multiple equilibria. In these equilibria, an increase in the visibility of performance, an increase in the sensitivity of performance to effort, and an increase in the informativeness of performance about talent may or may not boost the signaling incentive of programmers depending on the stability of equilibrium and on the properties of the probability that successful performance will be observed.
Keywords: 330; Open Source; EDV-Berufe; Karriereplanung; Leistungsmotivation; Signalling; Theorie